IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA/I DI SEKOLAH DASAR ISLAM AL-HIDAYAH KELURAHAN GANDASARI KECAMATAN JATIUWUNG KOTA TANGERANG - Ahmad Zulkarnaen ,; Sri Rahayu Ningsih, (UNISAN JURNAL, 2024)
The provision of education for the development of students' character education is conducted in a scheduled and flexible manner, taking into account the progress of learning activities, depth, and rhythm in learning. This activity is carried out with guidance from mentors who are experts in their respective fields, and teachers can take on roles in completing the learning program. The research questions in this study are: How is the implementation of character education management, what obstacles are encountered, and what efforts are made to overcome the obstacles in developing the interest, attitudes, and positive behavior of students at Al-Hidayah Jatiuwung Islamic Elementary School? The objectives of this research are to determine the implementation of character education management, identify the obstacles encountered, and explore the efforts made to overcome these obstacles in developing the interest, attitudes, and positive behavior of students at Al-Hidayah Jatiuwung Islamic Elementary School. Data were collected through observations, in-depth interviews, and document analysis. The results of the study indicate that the management of character education at Al-Hidayah Islamic Elementary School is carried out through several stages: planning, implementation, evaluation, and follow-up. In the planning stage, the school formulates the character values to be instilled, such as honesty, discipline, responsibility, and cooperation. The implementation of character education is integrated into learning activities as well as extracurricular activities, such as scouts, religious activities, and school cleanliness programs. Evaluations are conducted periodically to measure the development of students' character, involving teachers, parents, and the students themselves.